2012
DOI: 10.1037/a0028898
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of therapist variability: Therapist effects and the contribution of patient severity and risk.

Abstract: The size of therapist effect was similar to those found elsewhere, but the effect was greater for more severe patients. Differences in patient outcomes between those therapists identified as above or below average were large, and greater therapist risk caseload, rather than non-risk caseload, was associated with poorer patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
157
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 152 publications
(171 citation statements)
references
References 62 publications
10
157
1
3
Order By: Relevance
“…This extended range held even when a standardization procedure based on the average impairment of a clinical reference sample was implemented to control for the impact of initial impairment. Initial patient severity was found to be a significant predictor in all naturalistic datasets as well as in the integrated total dataset, which replicates former research (Saxon & Barkham, 2012). Additionally, in all eight datasets we consistently found the random slope model to be significantly superior as compared to the fixed slope model.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…This extended range held even when a standardization procedure based on the average impairment of a clinical reference sample was implemented to control for the impact of initial impairment. Initial patient severity was found to be a significant predictor in all naturalistic datasets as well as in the integrated total dataset, which replicates former research (Saxon & Barkham, 2012). Additionally, in all eight datasets we consistently found the random slope model to be significantly superior as compared to the fixed slope model.…”
Section: Discussionsupporting
confidence: 72%
“…In sum, the size of the TE in the three-level MLM was comparable to the findings in the most recent meta-analysis in this field, which suggested that approximately 7% of the variance in outcome was associated with therapists in naturalistic study designs (Baldwin & Imel, 2013). In addition, the distribution of therapist effectiveness was akin to that reported by Saxon and Barkham (2012), although our data revealed approximately 10% more therapists to be average. Although variations in sample sizes across datasets may partially explain the range of TEs in the current study sample, it is unlikely to be the only source of variability across datasets.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The residual for each therapist represents the degree to which a therapist's outcomes depart from those of the average therapist while controlling for patient characteristics (case-mix) and can be seen as the additional, unexplained impact of the therapist on & Spiegelhalter, 1996;Rasbash et al, 2009;Saxon & Barkham, 2012).…”
Section: Discussionmentioning
confidence: 99%